(untitled) (Tempo e Argumento, 2011)
This article aims at discussing the role of the two first international sports competitions held in Brazil in 1919 and 1922 in the country’s international relations scenario. By analyzing Brazilian foreign affairs, diplomatic actions and the reverberation of these events in the press, inside and outside the country, we try to make a first move to the understanding of these competitions as important steps in the country’s trajectory in holding international sports events and relevant aspects of Brazilian foreign policies.